Intense Acute Swimming Induces Delayed-Onset Muscle Soreness Dependent on Spinal Cord Neuroinflammation - Borghi, Sergio M.; Bussulo, Sylvia K. D.; Pinho-Ribeiro, Felipe A.; Fattori, Victor; Carvalho, Thacyana T.; Rasquel-Oliveira, Fernanda S.; Zaninelli, Tiago H.; Ferraz, Camila R.; Casella, Antônio M. B.; Cunha, Fernando Q.; Cunha, Thiago M.; Casagrande, Rubia; et al. (Frontiers in Pharmacology, 2022)
Unaccustomed exercise involving eccentric contractions, high intensity or long duration are recognized to induce delayed onset muscle soreness (DOMS). Myocyte damage and inflammation in affected peripheral tissues contribute to sensitize muscle nociceptors leading to muscle pain. However, despite the essential role of spinal cord in the regulation of pain, the spinal cord neuroinflammatory mechanisms in intense swimming-induced DOMS remained to be investigated. We hypothesized that spinal cord neuroinflammation contributes to DOMS. C57BL/6 mice swam for two hours to induce DOMS and nociceptive spinal cord mechanisms were evaluated. DOMS triggered the activation of astrocytes and microglia in the spinal cord 24 hours after exercise compared to the sham group. DOMS as well as DOMS-induced spinal cord NFκB activation were reduced by the intrathecal treatments with glial inhibitors (fluorocitrate, α-aminoadipate, and minocycline) and NFκB inhibitor (pyrrolidine dithiocarbamate; PDTC). Moreover, DOMS was also reduced by intrathecal treatments targeting CX3CL1, TNF-α, and IL-1β or with recombinant IL-10. In agreement, DOMS induced the mRNA and protein expressions of CX3CR1, TNF-α, IL-1β, IL-10, c-Fos and oxidative stress in the spinal cord. All these immune and cellular alterations triggered by DOMS were amenable by intrathecal treatments with glial and NFκB inhibitors. These results support a role for spinal cord glial cells, via NFκB, cytokines/chemokines and oxidative stress, in DOMS. Thus, unveiling neuroinflammatory mechanisms by which unaccustomed exercise induces central sensitization and consequently DOMS.